2017
DOI: 10.4103/jcrt.jcrt_90_17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of risk factors on stomal recurrence after total laryngectomy for laryngeal carcinomas: A meta-analysis

Abstract: In this study, we proved that subglottic location, advanced tumor stage, especially T4 stage, and preoperative tracheostomy were risk factors for SRAL for larynx cancer. However, many other potential risk factors, such as surgical margins, could not be determined for inadequate records. Hence, more prospective trials should be designed to determine the risk factors for SRAL for larynx cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The ARHQ methodology checklist is applicable for observational studies, including 11 items with a yes/no/unclear response option: Yes would be scored 1, no or unclear was scored 0, and an individual study can have a maximum of 11 quality points. Studies were deemed to be low quality (0-3), moderate quality (4)(5)(6)(7), and high quality (8-11). 6,7…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ARHQ methodology checklist is applicable for observational studies, including 11 items with a yes/no/unclear response option: Yes would be scored 1, no or unclear was scored 0, and an individual study can have a maximum of 11 quality points. Studies were deemed to be low quality (0-3), moderate quality (4)(5)(6)(7), and high quality (8-11). 6,7…”
Section: Data Extractionmentioning
confidence: 99%
“…To the best of our knowledge, only 1 systematic review of this topic has been published, in 2013 in a Chinese journal, which reported that transglottic location, tumor T-staging, and preoperative tracheotomy were important risk factors of recurrence after total laryngectomy. 5 Discouragingly, authors from other countries cannot access this review due to the lack of an English version of this review. We wished to update the systematic review of this topic in English and provide the information for more authors in the world.…”
Section: Introductionmentioning
confidence: 99%
“…PSR for laryngo-hypopharyngeal SCC is regarded, after distant metastases, as one of the most serious complications following TL, and is almost universally fatal [5]. Studies reported over the decades have identified several potential risk factors leading to PSR and many have proposed that the occurrence can and should be minimized if not prevented [6,7 ▪ ,8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, peristomal recurrence is a severe complication and has a high mortality rate. [4][5][6] In this study, we aimed to understand the clinical features of PSSCC that may warrant a bilateral level VI lymph node dissection. To this end, we analyzed the clinical features and pathological presence or absence of level VI lymph node metastasis in patients with PSSCC.…”
Section: Introductionmentioning
confidence: 99%